Методологія проектування Arduino в якості Web-client та Web-server з використанням датчика DHT11 та їх порівняльна характеристика - Лубко, Дмитро Вікторович; Литвин, Юлія Олександрівна (НТУ "ХПІ", 2017)
У статті проаналізовано можливість використання мікроконтролеру Arduino в двох режимах: веб-сервер та веб-клієнт, які слугують основою для розробки автономних інтерактивних приладь або може працювати під управлінням програмного забезпечення, встановленого на з’єднаному з ним комп’ютером. Розроблений програмний засіб має такі комплектуючі, як: Arduinouno, Ethernetshield, DHT11, резистор та проводи типу "мама-папа", "папа-папа". Представлений код програми дає змогу порівняти два режиму роботи Ардуіно та виявити їх певні переваги та недоліки в плані передачі, зберігання та відображення певних даних для користувача.

Currently, there is a significant increase in interest in Smart House technology. The issue of availability and ease of monitoring of the management of a smart house is of crucial importance. An owner or a user of a smart house should have access to all systems, be able to manage them remotely and receive information about the status of each of them on a 24-hour basis. Therefore, the question of implementation of monitoring of the received data from sensors arises. This paper discusses the choice between using Arduino as a server or a client. The purpose of this work is to provide a program for processing temperature and humidity data using Arduino as a web server and a web client and conducting their comparative characteristics in terms of speed and quality of transmission and data display. In the context of this work, the following functions should be performed: processing the received temperature data, humidity of the room from the sensor DHT 11 and displaying data in the browser. As a result of the work, the basic principles of Arduino's work as a web server and web client are analyzed. The "Server" class creates a server that can transfer data and receive data from connected clients (users). The "Client" class creates clients that can connect to servers and exchange data that connects to the server by the IP address and port specified in the parameters. In the aspect of monitoring, according to the results obtained on the web page, we can conclude that using Arduino as a web client is more appropriate because it allows the developer to create data display in a more user-friendly form for the user. In the aspect of data storage it is better to use Arduino as a web client, since the resulting data will be stored in the developed database, in our case phpMyAdmin. All this allows monitoring of the received data from any "Smart House" equipment.
Methodology of Arduino designing as a Web-client and Web-server with the use of the DHT11 sensor and their comparative characteristics
Keywords: мікроконтролер; веб-сервер; веб-клієнт; автономні інтерактивні прилади; програмне забезпечення; Arduino; Ethernet shield